Implementasi Sistem Pencarian Wisata Menggunakan Tour Talk Share (TTS) Berbasis Android Pada Provinsi Sulawesi Selatan (Komputika : Jurnal Sistem Komputer, 2021)
South Sulawesi is one of the provinces in Indonesia, located in the southern part of Sulawesi with the capital Makassar city which has many very interesting tourist attractions. So far, there have been many applications or website pages that introduce tourist attractions in South Sulawesi province, but they can only display an explanation of tourist attractions and their locations in the form of maps. The problem in this study is that there are several systems used but the scope of tourism is still limited, namely only aimed at one district or city, then how to use the Chat, Sharing, and Video features in the travel search application, Furthermore, how to help tourists communicate with each other in traveling in South Sulawesi province and how to design a tourism search system using Tour, Talk, Share based on android mobile in South Sulawesi province. The aim of this research is to design a tourist attraction search system in the province of South Sulawesi, create a system with the addition of chat features, sharing features, and features such as the ability to watch videos that are useful in finding tourist objects and being able to communicate with each other and implementing the tour system. Talk, share with android technology on your way to help tourists. The method and technology used in this study are mobile android, mobile is an object that is high-tech and can move without using cables and android is a linux-based operating system designed for touch screen mobile devices such as smartphones and tablet computers. The result of this research is that the application of the Android-based tour talk share (TTS) tourism system in South Sulawesi Province can help tourists get more detailed tourist information with more complete features.